Major determinants of the transfer of training: Implications for enhancing sport performance - Christina, R. W. (Human performance determinants in sport, 1996)
The motor learning literature was reviewed and the factors which affect the transfer of skill items learned at training/practice to competitive settings were identified and summarized. This summary highlights the general principles underlying skill training/practice which need to be contemplated when designing activities that havethe potential to benefit competitive performances.